The spread and clinical impact of ST14CC-PBP3 type IIb/A, a clonal group of non-typeable Haemophilus influenzae with chromosomally mediated β-lactam resistance—a prospective observational study. (March 2017) - Månsson, V.; Skaare, D.; Riesbeck, K.; Resman, F.
Abstract: Objectives: Increasing incidences of non-typeable Haemophilus influenzae (NTHi) with β-lactam resistance mediated through mutations in penicillin-binding protein 3 (BLNAR or rPBP3) have been observed in the past decades. Recently, an rPBP3 NTHi sequence type (ST) 14 with PBP3 type IIb/A caused a disease outbreak in a nursing home in Sweden with severe outcomes, indicating increased bacterial virulence. In this prospective observational study, the epidemiology and clinical significance of the corresponding clonal group (ST14CC-PBP3IIb/A) in Skåne, Sweden was investigated. Methods: ST14CC-PBP3IIb/A isolates were identified through partial multilocus sequence typing and ftsI (PBP3 gene)-sequencing of prospectively collected H. influenzae from patients with respiratory tract or invasive infections ( n  = 3262) in 2010–2012. Data on type of infection, hospitalization and outcomes were analysed, and the geographical distribution of isolates from different groups was investigated. Results: Isolates belonging to ST14CC-PBP3IIb/A constituted 26% ( n  = 94/360) of respiratory tract rPBP3 NTHi. From mapping of patient addresses, a dynamic geographical spread was apparent during the study period. Furthermore, patients with infections by ST14CC-PBP3IIb/A isolates had higher hospitalization rates compared with patients infected with other rPBP3 NTHi (14/83 versus 21/255, p 0.025) and to a group of patients infected with susceptible NTHi (14/83 versus 13/191, p 0.010). ST14CC-PBP3IIb/A isolates constituted 25% ( n  = 2/8) of invasive rPBP3 NTHi during the study period. Conclusions: Our investigation suggests that the ST14CC-PBP3IIb/A clonal group is associated with increased clinical virulence, resistance to several antimicrobial agents, and is persistent over time. We conclude that virulence varies between different NTHi, and that NTHi disease may be more dependent on bacterial factors than previously recognized.